PSYCHOLOGICAL STUDY OF ANXIETY IN PEOPLE WITH NICOTINE ADDICTION - Шинкаренко, Інна; Лукомська, Аліна (SWorldJournal, 2024)
The study is devoted to the study of the relationship between nicotine addiction and anxiety, which is an important aspect of the modern psychology of addictive behavior. Despite numerous warnings about the dangers of smoking, its prevalence remains high